National waiting time monitoring in oral healthcare - The role of triage dental nurses - Söderlund, Riitta (Sage, 2026)
OBJECTIVES: Our study analyzed dental nurses' use and use behavior determinants of electronic patient IS modules in telephone triage. The modules were implemented in public oral healthcare organizations' patient ISs to digitalize the national waiting time monitoring system.
METHODS: For the cross-sectional survey, we collected data from dental nurses using convenience sampling and applied a modified UTAUT as the theoretical framework.
RESULTS: The results indicate that using the module for different purposes varied, and the nurses used it sparsely in recording data for monitoring national waiting times. Using the module was laborious, and triage work was busy.
CONCLUSION: Dental nurses' low system usage resulted in poor-quality data for waiting time monitoring. As healthcare data is increasingly used for purposes other than clinical decision making, we must ensure that healthcare professionals performing clinical tasks perceive data recording for non-clinical purposes as meaningful and have time for proper data entry.